Adhesive joint properties of advanced carbon/ceramic composite and tungsten–copper alloy for the hybrid rocket nozzle. (October 2020) - Zhu, Yang; Zhang, Qiang; Meng, Xiangli; Yan, Liansheng; Cui, Hong
Abstract: A hybrid rocket nozzle is made up of several different functional components using different materials. The joint properties of these different parts are critical to ensure the service reliability and robustness of the nozzle structure. In this paper, three kinds of anti-ablation materials were selected, bonded together, then tested to assess their joint bonding capability in a hybrid rocket motor. Boron containing phenol-formaldehyde with 40 wt% SiC powder was used as adhesive on fine woven punctured felt preform carbon/ceramic composite (punctured ceramic), needled carbon cloth/felt layers preform carbon/ceramic composite (needled ceramic), and tungsten-copper alloy (W–Cu alloy). Thermogravimetric (TG) and differential scanning calorimetry (DSC) tests were conducted to characterize the high temperature performance of the adhesive. Scanning electron microscopy (SEM) and optical microscope images of the hybrid joints were used to find the failure mechanisms and failure propagations. The cohesion failure mode applied to all test specimens indicated that failure occurred in the adhesives, while the mechanical test of these hybrid joints showed that the needled ceramic/W–Cu alloy has the highest shear strength of 13.79 MPa. The demo firing test was used to demonstrate the joints behavior in a real environment. The results showed that the adhesive gap was strong enough to withstand the shear stress caused by combustion flow, and was capable of bearing 200 s of burning ablations.